The Night Club - Jenkins, Herbert George, 1876-1923 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Night Club" by Herbert George Jenkins is a novel written in the early 20th century. This light-hearted and humorous tale revolves around a group of friends, particularly the engaging character Bindle, who propose the formation of a story-telling club in London, called the Night Club. As the club forms and members gather each Sunday, comical exchanges, personal quirks, and the ensuing camaraderie form the heartbeat of the narrative. At the start of the book, we are introduced to the concept of the Night Club and its aim of storytelling among a diverse group of men, primarily consisting of acquaintances from the London hospital "Tims." Bindle, who thrives on laughter and life$1 (Bs jest, leads the charge in forming this unique gathering. As the members share their tales, we see personalities come to life, notably that of Sallie, a captivating woman who eventually becomes the only female member of the club. The stories and interactions set the tone for a whimsical exploration of friendship, clever wit, and societal observations during the backdrop of World War I. (This is an automatically generated summary.)s
Forming the Night Club -- The coming of Sallie -- The Prime Minister decides to advertise -- The boy -- The Barabbas Club -- I fail the Night Club -- A surprise behind the veil -- The making of a man of genius -- Mrs. Biltox-Jones's experiment -- The Night Club visits Bindle -- The general becomes a member -- The Mater -- The romance of a horsewhipping -- Ginger visits the Night Club -- A dramatic engagement -- The Moggridges' Zeppelin night -- Sallie at the wheel.
Release date is 2016-07-16
Produced by Al Haines
Keywords: Humorous stories; Storytelling -- Fiction; Short stories, English; World War, 1914-1918 -- England -- Fiction; Bindle, Joseph (Fictitious character) -- Fiction; Clubs -- Fiction